Peningkatan Kapasitas SDM dalam Pengembangan Pemasaran di Era Digital untuk UMKM di Desa Air Batu Kota Palembang - Noviyanti, Iis; Asmalah, Lia; Hayati, Feb Amni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting local economies, yet many still face challenges in marketing their products effectively, particularly in adapting to the digital era. In response to these challenges, a Community Service Program (PKM) entitled